Implementation of Facilities and Infrastructure Management in Early Childhood Learning at RA Al Bani Amir, Tangerang City, Banten - Muzdalifah; Cucu Atikah; Fahmi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to describe the implementation of facilities and infrastructure management in supporting children's learning processes at RA Al Bani Amir, Tangerang City, Banten. The research employed a qualitative approach using a descriptive method to obtain an in-depth understanding of the management of educational facilities and infrastructure implemented at the institution. The study was conducted during the second semester of the 2025/2026 academic year, involving the principal, teachers, and facilities and infrastructure manager as research participants. Data were collected through observations, interviews, documentation, and field notes. Data trustworthiness was ensured through triangulation techniques, member checking, prolonged engagement, persistent observation, negative case analysis, and peer debriefing. Data analysis was carried out in three stages: data reduction, data display, and conclusion drawing. The findings revealed that the implementation of facilities and infrastructure management encompassed planning, procurement, utilization, maintenance, inventory management, and evaluation. However, its implementation still encountered several challenges, resulting in suboptimal performance, particularly in the aspects of maintenance and facility organization. Nevertheless, the available facilities and infrastructure contributed positively to supporting children's learning by enhancing comfort, motivation, and engagement during learning activities. Therefore, facilities and infrastructure management plays a crucial role in improving the quality of early childhood education and should be managed more effectively, systematically, and sustainably.